Reactive strength index-modified: reliability, between group comparison, and relationship between its associated variables - Amilton Vieira; James J. Tufano (Termedia Publishing House, 2020)
To investigate and compare the reliability of reactive strength index-modified (RSImod) and its associated variables (jump height [JH] and [time to take-off]) 20 combat fighters and 18 physically active men participated in this study. They visited the laboratory three times; firstly, for jump familiarization and two sessions for test-retest (2-7 days apart). For both groups, the between-day changes in performance were trivial to small (≤ 1.1%). The coefficient of variation (CV) comparisons (i.e. CV ratio) demonstrated that combat athletes had a lower test-retest variation for RSImod (0.87) and JH (0.80) than non-athletes. Combat athletes demonstrated a greater JH than physically active men (0.43 vs 0.37; p = 0.03, g = 0.73), but small and non-significant differences were observed for RSImod (0.60 vs 0.55; p = 0.24, g = 0.38) and TTT (0.70 vs 0.72; p = 0.32, g = 0.33). RSImod was more positively correlated with JH (r = 0.75-0.87; p < 0.001) than negatively correlated with TTT (r = 0.45-0.54; p < 0.001). This study suggests that RSImod is a reliable variable obtained during CMJ testing in combat athletes and physically active men, with scores being slightly better for combat athletes. In terms of performance, combat athletes jumped higher than physically active men, but no differences in RSImod or TTT were observed. Lastly, RSImod was more strongly related to JH than TTT, and this was more evident in athletes than nonathletes. This indicates that the combat athletes were able to better utilize their (equal) time spent jumping (higher), possibly via greater utilization of the stretch shortening cycle, faster or more optimal motor unit recruitment, or an array of other factors.